Understanding Turnover Intention: Exploring the Influence of Job Security, Perceived Organizational Support, and Job Satisfaction as a Mediator - Diana Nafishah Putri,; Fatmah Bagis,; Tubastuvi, Naelati; Widhiandono, Hengky (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to examine the effect of independent variables, such as job security and perceived organizational support on the dependent variable, such as turnover intention and job satisfaction as mediation. This study uses a quantitative research design. Distributing questionnaires to employees of 4-star hotels in purwokerto. With a research duration of september-october 2023. The population in this study amounted to 276 employees. The sampling technique used in this study is the quota sampling method according to the proportion of each hotel. calculated using the slovin formula resulted in 176 respondents. the method used to analyze the data is to use smartpls 3.0. In this study, all instruments are valid and reliable. the results showed that job security has no effect on turnover intention. perceived organizational support has no effect on turnover intention. job satisfaction has no effect on turnover intention. job security has a positive and significant effect on job satisfaction. perceived organizational support has a positive and significant effect on job satisfaction. and job satisfaction does not mediate the relationship between job security and perceived organizational support on turnover intention. Job security is able to have a positive and significant influence on employee job satisfaction in 4-star hotels in purwokerto. in addition, organizational support perceived by employees at 4-star hotels in purwokerto can have a significant effect on job satisfaction. however, job satisfaction is not able to mediate the effect of job security and perceived organizational support on employee turnover intention.